Analysis of penicillamine using Cu-modified graphene quantum dots synthesized from uric acid as single precursor - Gema M. Durán; Tomás E. Benavidez; Ana M. Contento; Angel Ríos; Carlos D. García (Elsevier, 2017)
A simple methodology was developed to quantify penicillamine (PA) in pharmaceutical samples, using the selective interaction of the drug with Cu-modified graphene quantum dots (Cu-GQDs). The proposed strategy combines the advantages of carbon dots (over other nanoparticles) with the high affinity of PA for the proposed Cu-GQDs, resulting in a significant and selective quenching effect. Under the optimum conditions for the interaction, a linear response (in the 0.10-7.50 µmol/L PA concentration range) was observed. The highly fluorescent GQDs used were synthesized using uric acid as single precursor and then characterized by high resolution transmission electron microscopy, Raman spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, fluorescence, and absorption spectroscopy. The proposed methodology could also be extended to other compounds, further expanding the applicability of GQDs.